Hungary's Cold War : international relations from the end of World War II to the fall of the Soviet Union - Békés, Csaba (Chapel Hill : The University of North Carolina Press, 2022)
"In this magisterial and pathbreaking work, Csaba Békés shares decades of his research to provide a sweeping examination of Hungary's international relations with both the Soviet Bloc and the West from the end of World War II to the dissolution of the Soviet Union in 1991. Unlike many studies of the global Cold War that focus on East-West relationships--often from the vantage point of the West--Békés grounds his work in the East, drawing on little-used, non-English sources"--
Introduction -- The emerging Cold War -- Hungary's road to the Soviet bloc -- East Central Europe and the first phase of long détente, 1953-1956 -- Crisis year, 1956 : Poland, Hungary, Suez -- The international impact of the Polish and Hungarian revolts -- Hungary and the Soviet bloc in the Khrushchevian experimental era, 1956-1964 -- The main features of Kádárist foreign policy -- The German question and the CSCE process : foreign policy coordination and lobby fights in the Soviet bloc, 1964-1975 -- Standby détente : Hungary as the promoter of East-West relations -- The Soviet Union and East Central Europe, 1985-1990 -- The international context of the political transition in Hungary -- Epilogue: The end of the Soviet bloc.
Description based on print version record.
Includes bibliographical references (pages 390-365) and index.
JSTOR
Keywords: Cold War; Hungary -- Foreign relations -- Communist countries; Communist countries -- Foreign relations -- Hungary; Hungary -- Foreign relations -- Europe, Western; Europe, Western -- Foreign relations -- Hungary; Hungary -- Foreign relations -- United States; United States -- Foreign relations -- Hungary; Guerre froide; Hongrie -- Relations extérieures -- Pays socialistes; Pays socialistes -- Relations extérieures -- Hongrie; Hongrie -- Relations extérieures -- Europe de l'Ouest.; Europe de l'Ouest -- Relations extérieures -- Hongrie; Hongrie -- Relations extérieures -- États-Unis.; États-Unis -- Relations extérieures -- Hongrie; HISTORY / Europe / Eastern; Diplomatic relations; Communist countries; Hungary; United States; Western Europe; Politics & government; Politics and Government; Electronic books